(3QjGV GdeSGFds - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs ((3eMeO HGbQ Hf RjO GdYGHOjf GdjROjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3cJGH GdWgGQI hCQcGfg CQHYI, GdChd aj GdejGg LeYg HGYJHGQ (B.. (3CaQGOg hGdeQGO HgG GdCYe aj GdMbjbI hGdeLGR hGdfXQ aj GdeWdb hGdeVGas
(3BNQgG (B:s
(3BNQgG(B: (3hMedgG GdTjN Ydi ef aGJJg aj GdMVQ HCf jchf bO ONd Ydjg hbJgG bHd Cf jNQL hde jUdgG acGf Ydjg bVGDgG ajeG HYO hGSJTgO Ydjg HeG eQ Yf GdehKb hdG HCj Hg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 17s
(3GdPQjYI, L (B11: 240s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis